2019
DOI: 10.3390/sym11121495
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of AlGaN/GaN Heteroepitaxial Structure Fractal Geometry on Size Effects in Microwave Characteristics of AlGaN/GaN HEMTs

Abstract: The investigation of size effects appearing in the dependence of AlGaN/GaN HEMT high-frequency characteristics on channel width d and number of sections n is conducted using the notions of measure, metric and normed functional (linear) spaces. In accordance with the results obtained, in local approximation the phenomenon of similarity can exist, not only in metric spaces of heteroepitaxial structures, but also in the defined on them functional spaces of the measures of these structures’ additive electrophysica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…The observed size effects are due to the structural elements forming the OC having lateral inhomogeneities in their internal structure. As reported in [22,[30][31][32][33], it can be successfully described using the apparatus of fractal geometry.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The observed size effects are due to the structural elements forming the OC having lateral inhomogeneities in their internal structure. As reported in [22,[30][31][32][33], it can be successfully described using the apparatus of fractal geometry.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, it has been shown that the functional electrophysical properties of semiconductor materials (in particular, the resistive resistance of epitaxial GaN/AlGaN layers [22]) in the local approximation also exhibit scaling and statistical selfsimilarity properties. This made it possible to describe the size effects in the functional dependencies (conductivity) of semiconductor layers using the fractal geometry mathematical tool [22,23]. These facts suggest that the specific electrophysical characteristics of OCs to n-GaN should also obey similar laws.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Калибровка измерительных трактов портов осуществлялась по S-параметрам согласованием на проход ( " Thru"), на нагрузку 50 Ом (Load), на холостой ход ( " Open") и на короткое замыкание ( " Short"). После этого проводилась процедура дэ-эмбеддинга (de-embedding) и экстракция параметров эквивалентных элементов ЭС секции КЛП [13,14].…”
Section: объект исследований и методика экспериментаunclassified
“…Obviously, the variety of influence ways of various geometric forms of Brownian surfaces relief and their grain substructures on metal films functional characteristics is not fully realized yet. Specifically, it is proven by the existence of a number of nontrivial electrophysical properties based on lateral inhomogeneities extended to hundreds micron [31][32][33].…”
Section: Introductionmentioning
confidence: 99%